STRUKTUR NARATIF PADA FILM ANIMASI AVATAR THE LEGEND OF AANG: THE LAST AIRBENDER - Karla, Ellara (Capture : Jurnal Seni Media Rekam, 2010)
An analysis of narrative structure is as a media to understand to story and in the same time to deliver the mesassge and the meaning of the moral, cultural and religious values by the frame of education. In this case of Avatar The legend of Aang : The Last Airbender, narrative structure can provide the natural elements in every characters. The Natural element in which consist of water, ground, fire, air, is the mainly composition of making the characters. This kind of natural unsure is merely similar with daily Javanese living and as the energy representation in Javanese living. Keywords :Narrative structure, natural elements.